Improving Students' Learning Outcomes through the Application of Demonstration Method in Social Studies for Grade IV at SDN Gegeneng - Faradilla, Faradilla; Mutmainnatul Qolbiy, Iin; Salsabila, Syifa (Jurnal Primagraha, 2023)
Based on the pre-research results of the implementation of social studies learning (1) learning activities are still dominated by teachers so that students are less active in learning (2) the method used in social studies learning is the lecture method, where the information/concepts being studied are notified or presented by the method. lecture only; (3) in the learning process the teacher does not provide reinforcement in the form of providing motivation to students. The problem formulation in this study is "Whether the use of demonstration methods can increase social studies learning activities in class IV SD Negeri Gegeneng for the 2022/2023 academic year. The purpose of this study was to improve social studies learning activities in class IV SD Negeri Gegeneng for the 2022/2023 academic year. The results of the research on the social studies learning process using the demonstration method in class IV SD Negeri Gegeneng for the 2022/2023 academic year, were as follows: In cycle 1 teacher performance reached 67% and student activity reached 63%. In the second cycle, the teacher's performance reached 78% and student activity reached 71%. In the third cycle the teacher's performance reached 88% and student activity reached 92%.